2007
DOI: 10.1101/gad.1592807
|View full text |Cite
|
Sign up to set email alerts
|

Pin1 modulates RNA polymerase II activity during the transcription cycle

Abstract: . Using inducible Pin1 cell lines, we show that Pin1 overexpression is sufficient to release RNAP II from chromatin, which then accumulates in a hyperphosphorylated form in nuclear speckle-associated structures. In vitro transcription assays show that Pin1 inhibits transcription in nuclear extract, while an inactive Pin1 mutant in fact stimulates it. Several assays indicate that the inhibition largely reflects Pin1 activity during transcription initiation and not elongation, suggesting that Pin1 modulates CTD … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
88
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 54 publications
6
88
0
1
Order By: Relevance
“…1A). Bands (1), (2), and (3) were identified to be DNA-directed RNA polymerase II A, DNA-directed RNA polymerase IIB, and DNA-directed RNA polymerase I by the analysis using LC/MS, which agree with previous reports (23). Then we performed the immunoblotting using many antibodies to detect another protein included in the Pin1-containing complex because many faint bands were visible with silver staining.…”
Section: Identification Of Crtc2 In the Pin1-containing Complex Fromsupporting
confidence: 68%
“…1A). Bands (1), (2), and (3) were identified to be DNA-directed RNA polymerase II A, DNA-directed RNA polymerase IIB, and DNA-directed RNA polymerase I by the analysis using LC/MS, which agree with previous reports (23). Then we performed the immunoblotting using many antibodies to detect another protein included in the Pin1-containing complex because many faint bands were visible with silver staining.…”
Section: Identification Of Crtc2 In the Pin1-containing Complex Fromsupporting
confidence: 68%
“…In any case, both isomerases have important functions in transcription. Therefore, initiation-elongation transition is inhibited by Pin1 [196], whereas Ess1 affects multiple steps, such as initiation, elongation, 3′-end processing, and termination [197,[199][200][201]. In fact, it has been demonstrated that Ess1 promotes Ssu72-dependent function by creating the CTD structural conformation that is recognized by Ssu72 [202], and recently it has been confirmed that isomerization is a key regulator of RNAPII CTD de-phosphorylation at the end of genes [69].…”
Section: Hpin1 / Yess1mentioning
confidence: 99%
“…Yeast Ess1 physically interacts with the CTD [55,197], and it preferentially binds and isomerizes in vitro Ser5P residues [198]. Although Pin1 stimulates RNAPII CTD hyperphosphorylation, which results in transcription repression and inhibition of mRNA splicing [195][196], in vivo studies have proposed that Ess1 promotes RNAPII CTD de-phosphorylation. In any case, both isomerases have important functions in transcription.…”
Section: Hpin1 / Yess1mentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylations of Ser-2, ser-5 and ser-7 of the CTD are the major modifications but cistrans isomerization (Xu and Manley 2007) as well as serine and threonine glycosylation can occur. The multilayered phosphorylation of the CTD is brought about by a series of enzymatic activities during initiation and elongation.…”
Section: Rna Polymerase II Phosphorylation Is Altered On the Igh Genementioning
confidence: 99%